1973
DOI: 10.1073/pnas.70.9.2637
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Histones to Histone-Depleted Nuclei: Effect on Template Activity Toward DNA and RNA Polymerases

Abstract: The ability of histones to block the accessibility of DNA in chromatin to DNA and RNA polymerases was measured by addition of lysine-rich or arginine-rich histones to nuclei selectively depleted of these histones. By this procedure nuclei were obtained in which all of the original lysine-rich histone in the chromatin was replaced by arginine-rich histone. Conversely in other nuclei, additional lysine-rich histone replaced some of the endogenous arginine-rich histone. Lysine-rich histone was much more effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

1974
1974
1982
1982

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…Since we have ruled out any irreversible effects on DNase I digestion kinetics of the low-pH salt extraction procedure used to remove histones HI and H5 from erythroid nuclei, our results suggest that the lysine-rich histones HI and H5 have a marked effect on DNase I digestion kinetics. This is consistent with the findings of Silverman and Mirsky (1973) that removal of H1 histone from calf thymus nuclei greatly increases the rate of digestion with DNase I.…”
Section: Discussionsupporting
confidence: 92%
“…Since we have ruled out any irreversible effects on DNase I digestion kinetics of the low-pH salt extraction procedure used to remove histones HI and H5 from erythroid nuclei, our results suggest that the lysine-rich histones HI and H5 have a marked effect on DNase I digestion kinetics. This is consistent with the findings of Silverman and Mirsky (1973) that removal of H1 histone from calf thymus nuclei greatly increases the rate of digestion with DNase I.…”
Section: Discussionsupporting
confidence: 92%
“…In polyarginine complexes only a fraction of the side chains is effective, whereas in polylysine complexes all residues can be occupied by phosphates. Similar results have been obtained with lysine-rich and arginine-rich histones from studying the accessibility of DNase to DNA and chromatin [32,33] and of DNA polymerase to DNA in chromatin [34]. Lysine-rich histones block accessibility more effectively than arginine-rich histones.…”
Section: Resultssupporting
confidence: 70%
“…The chromatin of mammalian cell nuclei consists of DNA complexed with basic and acidic proteins which have long been suspected to be involved in control of the expression of the genetic material. Previous studies have shown that the nuclear DNA is quite extensively covered by the nuclear proteins and much of the genome is thus inaccessible to the actions of various enzymes, such as deoxyribonuclease (Pederson, 1972;Billings & Bonner, 1972;, RNA polymerase (Bonner & Huang, 1963;Silverman & Mirsky, 1973;Paul & Gilmour, 1969) and DNA polymerase (Silverman & Mirsky, 1973;Wang, 1969). Removal of the chromatin proteins removes the inhibiting influence and allows the enzymes to act on the DNA (Billings & Bonner, 1972;Silverman & Mirsky, 1973;Wang, 1969).…”
mentioning
confidence: 99%
“…Previous studies have shown that the nuclear DNA is quite extensively covered by the nuclear proteins and much of the genome is thus inaccessible to the actions of various enzymes, such as deoxyribonuclease (Pederson, 1972;Billings & Bonner, 1972;, RNA polymerase (Bonner & Huang, 1963;Silverman & Mirsky, 1973;Paul & Gilmour, 1969) and DNA polymerase (Silverman & Mirsky, 1973;Wang, 1969). Removal of the chromatin proteins removes the inhibiting influence and allows the enzymes to act on the DNA (Billings & Bonner, 1972;Silverman & Mirsky, 1973;Wang, 1969). There is, however, some argument about the degree to which the DNA is covered by the histones and the degree to which the covering proteins interfere with the approach ofprobe molecules (e.g.…”
mentioning
confidence: 99%